2005
DOI: 10.1111/j.1460-9568.2005.04107.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to a predator on behaviour and serotonergic neurotransmission in different brain regions of C57bl/6N mice

Abstract: Clinical studies and animal models have provided evidence that stress and serotonin may play a role in the aetiology of psychiatric diseases such as depression and anxiety. In addition, reciprocal interactions between stress and serotonergic neurotransmission have been demonstrated. However, the relationships between stress, serotonin and behaviour are far from completely understood. In this integrative study, we aimed to elucidate the effect of the psychological stress model predator exposure on behaviour and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…All groups showed a rapid drop in C out to basal levels ( Figure 7C). Decrease rates were not significantly different across groups (F (2,17) = 0.30, P > 0.7; Figure 7C,G). However, visual inspection followed by exponential curve fits of the descending data revealed that KO-M and WT-M-ESC groups exhibited faster recoveries based on descending half-lives (F (2,17) = 3.9, P < 0.05) and mean lifetimes (time constants) (F (2,17) = 3.9, P < 0.05) ( Figure 7H,I).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…All groups showed a rapid drop in C out to basal levels ( Figure 7C). Decrease rates were not significantly different across groups (F (2,17) = 0.30, P > 0.7; Figure 7C,G). However, visual inspection followed by exponential curve fits of the descending data revealed that KO-M and WT-M-ESC groups exhibited faster recoveries based on descending half-lives (F (2,17) = 3.9, P < 0.05) and mean lifetimes (time constants) (F (2,17) = 3.9, P < 0.05) ( Figure 7H,I).…”
Section: Resultsmentioning
confidence: 67%
“…The parameter most commonly used to assess stimulated microdialysis data is area under the curve (AUC). 3,7,17,29,32 High-K + -induced serotonin overflow peak heights and slopes were also analyzed. 33 Serotonin overflow in response to the shortest 1 min high-K + pulse was detected in all WT-M subjects, whereas 4/5 mice in both the WT-F-PE and WT-F-MD groups exhibited detectable serotonin overflow.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular concentrations of 5-HIAA are thought to reflect the metabolism of newly-synthesised 5-HT, rather than reflecting metabolism of released 5-HT, and thus can be taken as an index for the effects of manipulations on the synthesis of this indoleamine . The 4 mm long dialysis membranes used in this study were implanted such that they just entered the hippocampus from a dorsal approach and, thus, that dialysis would take place over the whole depth of the hippocampus (illustrated in Beekman et al 2005). This part of the hippocampus receives serotonergic innervation from both the dorsal (DRN) and median raphé nucleus (MRN).…”
Section: Discussionmentioning
confidence: 99%
“…An important brain structure in the coordination of the stress response is the hippocampus. Importantly, hippocampal serotonergic neurotransmission in rodents responds to stressful challenges such as immune stress, exposure to a predator, novelty and forced swim stress (Kirby et al 1995;Linthorst et al 1995;Rueter and Jacobs 1996;Beekman et al 2005;Linthorst 2005a,b).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that forced swim stress increased Fos counts in the lateral septum, but chronic administration of imipramine and fluoxetine did not block the alteration [24]. Exposure to a predator increased serotonergic neurotransmission in the septum as well as in the hippocampus and prefrontal cortex [25]. Therefore, the increases in Fos counts in the lateral septum by chronic milnacipran might response to compensate stress, although this is a speculation.…”
Section: Discussionmentioning
confidence: 98%